STUDI EKSPERIMEN PELAT BETON BERTULANG PRACETAK SATU ARAH BERPENAMPANG “U” SEBAGAI ALTERNATIF STRUKTUR LANTAI - Ardika, I Nyoman; Salain, I Made Alit Karyawan; Sukrawa, I Made (JURNAL SPEKTRAN, 2019)
This research is motivated from the thought how to apply advantage-precast method and resolve deficiency conventional method in implementation of construction reinforced concrete slab structures multi-storey building. Therefore conducted preliminary experiments by making structure slab of some elements one way precast reinforced concrete slab.  From some preliminary experiments with the problems encountered, finally defined cross-section “U” upside down,  with f'c 15 MPa design and 1300 mm long with cross sectional size 320 mm x 150 mm x 40 mm, tensile reinforcement 2Ø5,6987 mm with yield stress of steel 188 MPa. In this research will be reviewed some problems, that is capability slab U to support service load until cracking moment,  maximum length U slab to support service load design until cracking moment, and  maximum length U slab to support service load design until maximum deflection.  These three problems completed by carrying out the load test by using water as a testing load and the physical properties of the material which is used for reinforced concrete. Based on the analysis of test data obtained U slab able to support three times service load design (4,310 N/mm) without cracking, maximum length U slab to support service load design without cracking is 2300 mm, and maximum length U slab to support service load until maximum deflection is 3302,6 mm.    Keywords : U-Slab, precast, slab structure